Kinesiology of the Human Gait - AKALAN, NAZİF EKİN; Angın, Salih (Elsevier, 2020)
Gait is one of the most complex functional activity which takes 7 years in average to learn and there are many factors such as music that is listened to, momentary psychogenic state, exhaustion, happiness, anger, etc. may affect the gait characteristics. Gait is a common activity in our daily lives. People who experience pain in only one phase of gait do not feel it only once a day. This situation is unacceptable for the human body and, thus, causes automatic, compensatory changes in a short time. In this section, the fundamentals of normal gait, its sub-phases, and the biomechanical events under these phases are explained.
Keywords: Gait; Gait Analysis; Kinematics; Kinetics; Pathology